Accommodation growth, dynamics, and the role of social media in promoting sustainable ecotourism to offbeat destinations and its impact - Sovan Chattopadhyay (Ecotourism and Environment Conservation, 2026)
Background: Ecotourism emphasizes community-based development and environmental conservation, with homestays playing an increasingly important role in offbeat rural destinations. The rapid expansion of homestays, supported by digital platforms, raises both development opportunities and sustainability concerns. Methods: This study analyzes homestay evolution, operational characteristics, and spatial patterns in Sillery Gaon, Darjeeling Himalaya, India. Data were collected in 2023 from 35 homestays using a structured questionnaire. GIS-based spatial analysis was applied, alongside an assessment of Google Trends Relative Search Index (RSI) and user- and brand-generated YouTube content from 2014–2023 to evaluate the influence of digital media on ecotourism demand. Findings: Homestay growth, initiated in 2008–2009, accelerated after 2016 with increasing reliance on tour operators and digital platforms. Homestay expansion shows a positive relationship with online search interest and social media content, while elevation exhibits a negative correlation with homestay distribution. Although homestays enhance tourism visibility and local livelihoods, their continued growth is associated with land-use and environmental impacts. Conclusion: Digital platforms are central to promoting offbeat ecotourism and supporting community-based development. However, unmanaged homestay expansion poses environmental challenges, highlighting the need for sustainable planning and regulation. Novelty/Originality of this article: This study integrates spatial analysis with digital media indicators to reveal the interlinkages between homestay growth, online visibility, and sustainable rural ecotourism in a Himalayan offbeat destination.